SISTEM INVENTARIS BERBASIS WEB DI KANTOR FAKULTAS SAINS DAN TEKNOLOGI UNIVERSITAS IBRAHIMY - Mukhlis Mukhlis; Firman Santoso (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The inventory management information system at the Faculty of Science and Technology (Saintek) at Ibrahimy University is designed to facilitate the management of assets, including the recording of incoming goods, outgoing goods, loans, and returns. This study uses a qualitative method with data collection techniques through observation, interviews, and literature review. The result of this study is an information system capable of managing inventory efficiently and effectively, as well as producing accurate and timely reports. The system is designed using Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD) to illustrate data flows and relationships between entities. With this system, it is expected to improve inventory management and support the smooth operation of the faculty